Is early detection of basal cell carcinoma worthwhile? Systematic review based on the WHO criteria for screening3. (24th May 2016) - Hoorens, I.; Vossaert, K.; Ongenae, K.; Brochez, L.
Summary: The incidence of basal cell carcinoma (BCC) has risen three‐ to fourfold over the last 30 years and is expected to continue to increase with ageing of the population. Although BCC has a good prognosis, it causes significant morbidity and has an important impact on the public health budget due to direct treatment costs. Based on the existing evidence, a systematic evaluation of the World Health Organization criteria was performed to determine whether earlier detection of BCC could reduce morbidity and cost. BCC slowly increases in size, with a median increase in diameter of 0·5 mm over 10 weeks. There is an important delay in diagnosis ranging from 19 to 25 months. In several studies BCC size was the main determinant of treatment cost, surgical complexity, reconstruction technique and the specific surgical procedure performed, such as Mohs micrographic surgery or surgical excision. One study showed that size also seems to affect the cost per treatment for other nonsurgical options. The use of vismodegib, an inhibitor of the hedgehog pathway, is confined to locally advanced or metastatic BCC. Delays in diagnosis and appropriate treatment are the most important underlying causes in the occurrence of giant BCC and/or BCC with metastasis. Although the latter represent only a very small fraction of all BCCs, the majority of them are located in the facial region. The available data point to a slow increase in the size of BCCs over time. Size is one of the major determinants in choice of treatment and the associated cost, especially for facial BCC. Therefore we conclude that current data support early detection and adequate management of BCCs on the face. Abstract : What's already known about this topic? Basal cell carcinoma (BCC) is the most common (skin) cancer in Europe. Its incidence is rising dramatically, and it is associated with an important direct treatment cost for healthcare budgets. BCCs slowly increase in size, with a median increase in diameter of 0·5 mm over 10 weeks. Delays in diagnosis and appropriate treatment are the most important underlying causes of giant BCC and metastasis. What does this study add? Early detection and starting of adequate treatment of BCC seem to be crucial for BCC of the face, more specifically in the H‐zone. Small changes in size can affect treatment options (e.g. type of surgery), their effectiveness and the associated costs. Linked Comment: Linos and Chren. Br J Dermatol 2016;174: 1181–1182 . Linked Comment: Wisco and Adelson. Br J Dermatol 2016;174: 1182–1183 . Plain language summary available online